Lecture 5: Building your plan - McMillan, G.
This lecture shows how to arrange the building blocks for optimal training in the proper order to build an individualized and optimal training schedule. You`ll first learn how to critique yourself. You`ll examine how your body responds and adapts to different types of training. Then, in Part II, you`ll see how I develop training programs "from the ground up". Using what you learn in Part I of the lecture, you can then build your training plan.